Hydrochemical of Groundwater and the Potential of Sea Water Intrusion in Tanah Laut, South Kalimantan (Proceedings of the International Conference of Geological Engineering Faculty, 2021)
The Tanah Laut area in South Kalimantan Province is a rapidly developing area, in linewith the plan to relocate the country's capital. Therefore, the need for groundwater as a waterresource in community life in that area needs to be supported by various studies. This research isintended as a hydrogeological survey in Tanah Laut District, to determine the local groundwaterhydrochemistry and its potential for sea water intrusion. The research was conducted in the field bycollecting data on the physical properties of groundwater in 155 dug wells and 50 artesian wells.Several groundwater samples representing free and confined aquifers were tested forphysical/chemical properties in the laboratory. The analysis was performed based on groundwatertable, pH, electrical conductivity (EC) and groundwater facies. The results showed that freegroundwater has a pH of 6.1 - 8.4 and a total dissolved solid (TDS) ranged from 20.3 - 964 μS/cm,while the confined groundwater had a pH of 4.01 - 9.95 and a TDS of 28 – 2,670 μS/cm.Groundwater facies vary widely, generally dominated by Na and bicarbonate ions. Brackishgroundwater was found in confined aquifers in two locations, namely Asam Jaya and Mekar Sari,indicating that the research area has the potential of sea water intrusion.
Keywords: Groundwater; Hydrochemical; Seawater Intrusion; Potential